2018
DOI: 10.21608/efmj.2018.68554
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Primary Dysmenorrhea among Secondary School Students and Its Treatment Modalities in Fayed City

Abstract: Background: Primary dysmenorrhea is a common problem of adolescent girls. It has a high prevalence in Egypt so it is important to evaluate the prevalence of dysmenorrhea and the treatment modalities used to alleviate it. Objective: To evaluate the prevalence of primary dysmenorrhea and its treatment modalities. Methods: This cross-sectional study was conducted on 95 students at four secondary schools in Fayed city from October to November 2017. Data were collected using a predesigned self-administered question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The most commonly chosen analgesics are those containing using ibuprofen, drotaverine, and paracetamol. Most of the study participants stated that they were satisfied with the pharmacotherapy effect (Tataj-Puzyna et al, 2021); (Ameade et al, 2018); (Ore & Ogundeko, 2021); (Owonaro et al, 2021); (Saka et al, 2018); (Kamel et al, 2017); (Karout et al, 2021); (Vlachou et al, 2019); (Gebeyehu et al, 2017); (Abdel-Sattar, 2018); (Söderman et al, 2019). One study showed that most respondents (86.14%) used prescription analgesics and over-the-counter medications.…”
Section: Pharmacologicalmentioning
confidence: 99%
“…The most commonly chosen analgesics are those containing using ibuprofen, drotaverine, and paracetamol. Most of the study participants stated that they were satisfied with the pharmacotherapy effect (Tataj-Puzyna et al, 2021); (Ameade et al, 2018); (Ore & Ogundeko, 2021); (Owonaro et al, 2021); (Saka et al, 2018); (Kamel et al, 2017); (Karout et al, 2021); (Vlachou et al, 2019); (Gebeyehu et al, 2017); (Abdel-Sattar, 2018); (Söderman et al, 2019). One study showed that most respondents (86.14%) used prescription analgesics and over-the-counter medications.…”
Section: Pharmacologicalmentioning
confidence: 99%